Reduction in the severity of early onset severe preeclampsia during gestation may be associated with changes in endothelial cell activation: A pathological case report. (2nd January 2016) - Chen, Q.; Sousa, J. De; Snowise, S.; Chamley, L.; Stone, P.
ABSTRACT: Early severe preeclampsia with changes consistent with the Hemolysis elevated liver enzymes low platelet count (HELLP) variant and severe fetal growth restriction rarely resolves prior to delivery. Established clinical disease is preceded by endothelial dysfunction and inflammation. Endothelial activation is reported in vitro to be raised in the presence of necrotic trophoblastic debris which is deported into the maternal circulation in preeclampsia. We report on an early severe preeclamptic patient admitted at 24 weeks gestation. Maternal serum was taken at day 2, 16, 30 of admission and 45 days postpartum. 20% maternal serum or trophoblastic debris from first trimester placental explants that had been cultured with 10% maternal serum was exposed to endothelial cells. Endothelial cell activation was quantified by the cell surface ICAM-1 expression and U937 monocyte adhesion assay. The clinical condition of this patient improved including the blood pressure, liver function, and platelet count by the 3rd day after antihypertensive treatment and remained normal until delivery at 37 weeks. ICAM-1 expression and U937 moncyte adhesion assay of endothelial cells was significantly increased following exposure of the endothelial cells to the maternal serum or trophoblastic debris from placentae treated with maternal serum drawn on day 2. However, ICAM-1 expression and the monocyte adhesion assay were significantly reduced following exposure of endothelial cells to maternal serum or trophoblastic debris from placenta treated with maternal serum drawn on day 16 or 30. Our data suggest unknown factor(s) in the maternal serum triggered endothelial cell activation when the clinical symptoms were present. The improvement in the clinical condition occurred along with the changes in endothelial cell activation.